The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2332858418819851
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teachers’ Emotions via Nonverbal Behavior During Video-Based Teacher Professional Development

Abstract: Increasing research on teacher professional development (TPD) has found teachers' self-reflection to be key for improving teaching effectiveness. Although video methodology, as often used in TPD, provides crucial insight concerning situated learning, teachers are often reticent to participate in TPD protocols due to discomfort over being videotaped. This longitudinal study explored emotion-related behaviors by assessing the nonverbal expressions exhibited by teachers during a 1-year videobased TPD program high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Affective state can be a critical mediator of teachers' attention, motivation and cognitive participation influencing how they engage in TPD type activities, including those which involve viewing of video from their own classrooms (Pekrun, 2006;C.-F. Chang et al, 2018). We have not been able to locate any studies on teachers' emotional responses to 360-degree video of their own classrooms.…”
Section: Discussionmentioning
confidence: 96%
“…Affective state can be a critical mediator of teachers' attention, motivation and cognitive participation influencing how they engage in TPD type activities, including those which involve viewing of video from their own classrooms (Pekrun, 2006;C.-F. Chang et al, 2018). We have not been able to locate any studies on teachers' emotional responses to 360-degree video of their own classrooms.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has focused on the emotions generated by teachers' interactions with partners in PD (Borko et al, 2008;10.3389/fpsyg.2022.1033988 Frontiers in Psychology 04 frontiersin.org Kleinknecht and Schneider, 2013;Parr and Hawe, 2017;Chang et al, 2018), with the interactions primarily taking the form of video-based teaching observation, discussion, and reflection. For example, Kleinknecht and Schneider (2013) showed that othersviewing corresponds to a more profound analysis of problematic events and higher emotional engagement, such as disappointment and anger, in their study of five pairs of mathematics teachers independently analyzing teaching video processes in a web-based environment.…”
Section: Teacher Emotions In Professional Development Programsmentioning
confidence: 99%
“…The findings also revealed that self-viewing necessitates more pre-existing scaffolding than others-viewing. In contrast, the emotions generated by teacher–mentor interactions have piqued the interest of only a few scholars ( Chang et al, 2018 ; Sun and Yang, 2021 ). Sun and Yang (2021) found in their study that teachers in PD felt confident when they received expert guidance and felt anxious when they believed they could not perform well.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of teacher professional development, we found that more and more research is focusing on teachers' learning processes, especially incorporating physiological and psychological data. For example, Chang et al (2018) explored teachers' emotional experiences by coding the nonverbal expressions of their recorded videos. Wolff et al (2016) investigated differences in how expert and novice teachers perceive problematic classroom scenes with eye-tracking technology.…”
Section: Introductionmentioning
confidence: 99%